Frequency of Factors Involved in Crowns and Fixed Partial Denture Failure (Medical Forum Monthly, 2020)
Objective: To determine the frequency of Crown and Fixed Partial Denture failure in Patients reported to Rehmat Memorial Hospital.Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was conducted at the Rehmat Memorial Post Graduate Teaching Hospital Women Medical & Dental College, Abbottabad from February 2018 to March 2019.Materials and Methods: Total 112 patients selected with Non-Probability Consecutive sampling technique reported with failure of Crown and Fixed Partial Dentures (FPD).Results: In our study gender distribution of patients was, males were 45 (40.17%) and females were 67(59.82%).The most common factor causing crown failure was periodontal problem (40%) while the least common was aesthetics (2%). While the most important factor causing failure in FPD was caries (35%) and the least was aesthetics (4%). Informed consent was obtained from all patients enrolled. Data was analyzed on SPSS 20 version. Chi-Square test was applied for Statistical significance.Conclusion: The main factor accounted for failure in crowns was periodontal problem, followed by caries, defective margins, cementation failure, loss of retention and poor aesthetics. While the most frequent factor associated with FPD failure was caries, followed by periodontal problems, loss of retention, defective margins, cementation and esthetics failure.